Biodiversity values of timber plantations and restoration plantings for rainforest fauna in tropical and subtropical Australia - Kanowski, J.; Catterrall, C.; Proctor, H.; Reis, T.; Tucker, N.; Wardell-Johnson, Grant (Rainforest CRC, 2005)
It has been suggested that timber plantations could play an important role in the conservation of biodiversity in cleared rainforest landscapes, not only because of their potential to cost-effectively reforest large areas of land, but also because they may provide habitat for rainforest plants and animals. However, this last claim is largely untested. In this study, we surveyed the occurrence of a range of animal taxa in monoculture and mixed species timber plantations and restoration plantings in tropical and subtropical Australia. We used the richness of 'rainforest-dependent' taxa (i.e., birds, lizards and mites associated with rainforest habitats) in reforested sites as our measure of their 'biodiversity value'. We also examined whether the biodiversity value of reforested sites was correlated with habitat attributes, including plant species richness and vegetation structure and, further, whether biodiversity value was affected by the proximity of reforested sites to intact rainforest.In general, our results showed that: young timber plantations (both monoculture and mixed species) supported few rainforest taxa; Birds associated with rainforests were poorly represented in young timber plantations, but were moderately common in restoration plantings; Few rainforest lizards were recorded in young reforested sites, except in restoration plantings in the tropics; Rainforest mites were generally detected more frequently in restoration plantings than cabinet timber plantations, while the richness of rainforest mites in monoculture plantations varied between regions; The richness of rainforest birds in young reforested sites was positively correlated with plant species diversity and structural complexity, with similar correlations observed for rainforest lizards in the tropics; Rainforest mite richness was poorly correlated with measured habitat variables; and that Monoculture plantations close to intact forest tended to support more rainforest birds, lizards and mites than isolated plantations.These results suggest that plantations are likely to have limited value for rainforest taxa under conditions which often characterise broadscale reforestation: i.e., when plantations are established on cleared land, at some distance from intact forest and when plantations are managed intensively for timber production. Management of plantations for their faunal biodiversity values is likely to require the development of explicit design, management and harvest protocols, such as the incorporation of habitat features into plantations and/ or the reservation or restoration of native forest on part of the plantation estate.